Industry requirement analysis for Malaysian IT graduates - Kalesamy, Kohila Malar (2005)
The study involves two main parts. The first part is focused on conducting an online initial study by gathering data in relation to industrial requirements of IT graduates, which are produced by higher learning institutions in Malaysia. Therefore, in order to fulfill this, three sets of online surveys were created to capture data from the IT graduates, institutions and industries. These surveys were posted online and the data sampling were collected for a period of time. The data collection from this part is later used by the second part of the project in which the results of the study are displayed. This second part is the development of a website which shall be used by the IT graduates, institutions of higher learning and industries as a point of reference, in a way that it could be used both as providing data and information as well as getting data and information. In this part too, the sampling data collected from the first part are analyzed by the developed system to produce various results reflecting the IT sector. Based on the results of the analysis produced by the system, various drawbacks between IT graduates, institutions and industries are identified and discussed. The main drawback indicates that there is no collaboration involved among the three entities which resulting in no cooperation and sharing of information. Therefore, in order to resolve these drawbacks, it is suggested that various strategies are identified and outlined in order to achieve collaboration among the IT graduates, institutions of higher learning and industries. The website can be identified as a meeting point to achieve collaboration among the three entities by which it provides data to the institution and IT graduates on what industry requires and at the same time it ensures that industry recruits the IT graduates with the relevant skills.